2014
DOI: 10.1016/j.celrep.2014.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Serine, but Not Glycine, Supports One-Carbon Metabolism and Proliferation of Cancer Cells

Abstract: Previous work has shown that some cancer cells are highly dependent on serine/glycine uptake for proliferation. Although serine and glycine can be interconverted and either might be used for nucleotide synthesis and one-carbon metabolism, we show that exogenous glycine cannot replace serine to support cancer cell proliferation. Cancer cells selectively consumed exogenous serine, which was converted to intracellular glycine and one-carbon units for building nucleotides. Restriction of exogenous glycine or deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
459
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 488 publications
(509 citation statements)
references
References 17 publications
23
459
0
1
Order By: Relevance
“…Dihydrofolate reductase provides THF, which is a precursor to 5,10-methylene-THF. On the other hand, the proliferation defect induced by the knockdown of amplified 3-phosphoglycerate dehydrogenase in triple-negative breast cancers could not be rescued with the supplementation of extracellular serine [42,43], despite the fact that extracellular serine can fuel folate metabolism [50]. Thus, increased supply of serine does not seem to be the critical function of 3-phosphglycerate dehydrogenase amplification.…”
Section: Triple-negative Breast Cancermentioning
confidence: 99%
“…Dihydrofolate reductase provides THF, which is a precursor to 5,10-methylene-THF. On the other hand, the proliferation defect induced by the knockdown of amplified 3-phosphoglycerate dehydrogenase in triple-negative breast cancers could not be rescued with the supplementation of extracellular serine [42,43], despite the fact that extracellular serine can fuel folate metabolism [50]. Thus, increased supply of serine does not seem to be the critical function of 3-phosphglycerate dehydrogenase amplification.…”
Section: Triple-negative Breast Cancermentioning
confidence: 99%
“…Recently, a number of studies have assessed the significance of serine and glycine metabolism in cancer cells. The complex, cyclical nature of serine and glycine metabolism can occur through cytoplasmic and mitochondrial pathways, both of which have been demonstrated to be upregulated in cancer cells (46)(47)(48)(49)(50). Additionally, serine and glycine metabolism converge on the formation of folate compounds, a target of chemotherapy for over sixty years (51)(52)(53).…”
Section: Mitochondrial and Amino Acid Metabolismmentioning
confidence: 99%
“…A recent study has suggested that cancer cells rely more on serine than glycine to support growth and metabolism 20 . A similar trend was observed in the five breast cancer cell lines we examined; serine supplementation of basal media enhanced the growth of all the cell lines, glycine supplementation increased growth of only one cell line, while formate did not affect the growth of any of the cell lines examined (Suppl.…”
Section: Generation Of Mcf-7 Cells With Stable Depletion Of Mthfd2mentioning
confidence: 99%